Improvement of Performance Range of Centrifugal Compressors Gas by Surge Line Modification Using Active Controller Based on Fuzzy Logic - Pezhman Mohammadi; Maryam Jedi; Farid Sheikholeslam; Mostafa Ghayour (Journal of Intelligent Procedures in Electrical Technology, 2012)
In this work, surge of prevention is a critical problem in oil and gas industries, particularly when return gas flow or gas flow reduces in transportation of gas pipelines. This paper is illustrated new results about surge control of centrifugal compressors .surge phenomenon is flow unsteady state in compressors which causes damages seriously in compressor construction. Furthermore, it also demonstrates in comparison with anti surge control ،active surge control expands stability range.Active surge control which based on fuzzy logic،is the main idea that used in this investigation. Using fuzzy controller causes an improvement in compressor's condition and increase performance range of the compressor, in addition to prevention of any instability in compressor. The simulation results is also satisfactory.